Control Automation for Ferrous Alloy Casting - Ovechkin, Maxim V.; Galina, Lubov V.; Chernousova, Antonina M. (2022 International Conference on Industrial Engineering, Applications and Manufacturing (ICIEAM), 2022)
This paper reviews the development of an automated control system for ferrous alloy casting based upon the research of this process. The relevance of the topic is due to the growth of steel production in the world. The authors built a configuration for automated production process control systems. The subject of the study is automation of the technological process of casting ferroalloy. Detail for production process control algorithms are provided as a Function Block Diagram. Has been developed a diagram of the vector control system of electric motors based on current control. The mnemonic diagram of the casting operator in Simle-Scada is presented.